Adalimumab for the treatment of cardiac sarcoidosis with multiple arrhythmias. (31st August 2022) - Li, Sitong; Wang, Hui; Liu, Tong; Li, Qifan; Yang, Xiuxiu; Xiong, Ran; Lv, Qiang; Du, Xin; Dong, Jianzeng; Ma, Changsheng
Abstract: A 45‐year‐old male with cardiac sarcoidosis verified by cardiac biopsy presented with multiple coexisting arrhythmias, including ventricular tachycardia of more than 1000 episodes per 24 h, paroxysmal atrial fibrillation, and third‐degree atrioventricular block. He did not respond to corticosteroids dose of 20–60 mg once daily and mycophenolate mofetil dose of 1 g twice daily for 6 months. Cardiac magnetic resonance (CMR) demonstrated inflammation and late gadolinium enhancement on right ventricular wall and interventricular septum. Positron emission tomography‐computed tomography (PET‐CT) showed multifocal 18 F‐fluorodeoxyglucose uptake in the heart. We replaced mycophenolate mofetil with adalimumab, a tumour necrosis factor‐α inhibitor. After 3 months, his arrhythmias improved significantly, manifesting as premature ventricular contractions of only 500 beats per 24 h and first‐degree atrioventricular block. CMR showed a significant reduction in inflammation and late gadolinium enhancement, and PET‐CT showed a complete resolution of fluorodeoxyglucose uptake.